2018
DOI: 10.1177/1756829318794167
|View full text |Cite
|
Sign up to set email alerts
|

Exploring tandem wing UAS designs for operation in turbulent urban environments

Abstract: The stability of small unmanned air systems can be challenged by turbulence during low-altitude flight in cluttered urban environments. This paper explores the benefits of a tandem wing aircraft configuration with the implementation of a pressure-based phase-advanced turbulence sensory system on a small unmanned air system for gust mitigation. The objective was to utilise passive and active methods to minimise gust-induced perturbations. Experimentation in repeatable turbulence within a wind tunnel's test sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…SD2020, the MDAO tool adopted for the present research, has been developed at Pisa University starting from the research reported in [11,12], in which procedures and tools for the preliminary design solar powered HALE UAVs have been implemented in a MATLAB environment. The tandem-wing architecture has been investigated in a number of papers dealing with several aspects of its applications to UAVs, such as design and test of VTOL drones [17], stability in turbulent flows [18], aerodynamics of tube-launched devices [19], whereas, to the best of authors' knowledge, there is a lack of literature about the adoption of solar powered propulsion.…”
Section: Overview Of Sd2020mentioning
confidence: 99%
See 1 more Smart Citation
“…SD2020, the MDAO tool adopted for the present research, has been developed at Pisa University starting from the research reported in [11,12], in which procedures and tools for the preliminary design solar powered HALE UAVs have been implemented in a MATLAB environment. The tandem-wing architecture has been investigated in a number of papers dealing with several aspects of its applications to UAVs, such as design and test of VTOL drones [17], stability in turbulent flows [18], aerodynamics of tube-launched devices [19], whereas, to the best of authors' knowledge, there is a lack of literature about the adoption of solar powered propulsion.…”
Section: Overview Of Sd2020mentioning
confidence: 99%
“…In this case, the application of the box-wing to solar UAVs (Figure 3-right) aims to obtain a reinforced tandem-wing in which the joiners act at the same time as stiffeners, aerodynamic surfaces and solar panels. The tandem-wing architecture has been investigated in a number of papers dealing with several aspects of its applications to UAVs, such as design and test of VTOL drones ( [17]), stability in turbulent flows ( [18]), aerodynamics of tube-launched devices ( [19]), whereas, to the best of authors' knowledge, there is a lack of literature about the adoption of solar powered propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it can serve as inspiration for the following achievements. The bio-inspired system for sensing of atmospheric disturbances on vehicle's wing was introduced by Mohamed [5][6][7], and further experimentally tested for disturbance rejection [8][9][10][11]. Furthermore, real-time information on the angle of attack from wing pressure measurements in the purpose of wind field estimation was demonstrated by Gavrilovic [12].…”
Section: Related Researchmentioning
confidence: 99%
“…Assuming the vertical wind component is much less than the forward airspeed, optimal flight path angle is close to 45°. (2) Energy maximization in presence of vertical wind shear ∂w z /∂x would imply climbing into a positive gradient and descending into a negative gradient with optimal flight path angle shown in equation (11).…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…The control mechanisms and sensing strategies used to maintain this stability are not understood. Studies investigating the control strategies employed by windhovering birds would likely discover novel gust-mitigation techniques that inspire the development of ultra-stable UAVs, a concept that has been a research focus of our group [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%